POTENSI KERUGIAN EKONOMI KARENA STUNTING PADA BALITA DI INDONESIA TAHUN 2013 - Renyoet, Brigitte Sarah; Martianto, Drajat; Sukandar, Dadang (Jurnal Gizi dan Pangan, 2016)
The research objective was to estimate the amount of economic potential losses due to stunting in toddlers in Indonesia. This is a descriptive research using secondary data in 2013 from various relevant institutes. Data was collected from Indonesia's Ministry of Health and Central Bureau of Statistics (CBS). Calculation from Konig (1995) and a correction factor of the Horton (1999). The results of the study that the average economic potential losses in 32 provinces in Indonesia was around Rp 96 billion-Rp 430 billion (0.15-0.67%) of the GRDP average of the provinces in Indonesia. Total cost for economic potential losses due to low productivity stunting in toddlers in Indonesia was around Rp 3,057 billion-Rp 13,758 billion (0.04-0.16%) of the total GDP of Indonesia.Keywords: economic potential losses, stunting, toddlers